Risk of Introduction of Bovine Tuberculosis (TB) Into TB-Free Herds in Southern Bahia, Brazil, Associated With Movement of Live Cattle - Avila, Luciana N.; Gonçalves, Vitor S. P.; Perez, Andres M. (Frontiers in Veterinary Science, 2018)
Bovine tuberculosis (TB) is a zoonotic disease, endemic in Brazil, with an impact on public health and trade. TB causes direct and indirect financial losses to infected farms and regions. Our study aimed at quantifying the risk of introduction of TB into TB-free herds of southern Bahia, Brazil, via movement of live cattle from other regions of the State. Results suggest that the annual risk of introducing TB into free farms of southern Bahia, either through legal or illegal trade of live cattle, is very low, varying, on average, between 0.001 and 0.006 depending on the region of origin of the animals. Noteworthy, illegal movements accounted for 90% of the risk demonstrating the importance of compliance with official regulations. These results are useful to inform both veterinary authorities and farmers in making decisions on TB control and the purchase of animals, with the ultimate goal of eliminating this major zoonotic disease from an important dairy region of Brazil.